Randomized clinical trial of biodegradeable intraluminal sheath to prevent anastomotic leak after stapled colorectal anastomosis. Issue 8 (10th May 2017) - Bakker, I S; Morks, A N; ten Cate Hoedemaker, H O; Burgerhof, J G M; Leuvenink, H G; van Praagh, J B; Ploeg, R J; Havenga, K; ,; Bakker, I S; Morks, A N; ten Cate Hoedemaker, H O; et al.
Abstract: Background: Anastomotic leakage is a potential major complication after colorectal surgery. The C-seal was developed to help reduce the clinical leakage rate. It is an intraluminal sheath that is stapled proximal to a colorectal anastomosis, covering it intraluminally and thus preventing intestinal leakage in case of anastomotic dehiscence. The C-seal trial was initiated to evaluate the efficacy of the C-seal in reducing anastomotic leakage in stapled colorectal anastomoses. Methods: This RCT was performed in 41 hospitals in the Netherlands, Germany, France, Hungary and Spain. Patients undergoing elective surgery with a stapled colorectal anastomosis less than 15 cm from the anal verge were eligible. Included patients were randomized to the C-seal and control groups, stratified for centre, anastomotic height and intention to create a defunctioning stoma. Primary outcome was anastomotic leakage requiring invasive treatment. Results: Between December 2011 and December 2013, 402 patients were included in the trial, 202 in the C-seal group and 200 in the control group. Anastomotic leakage was diagnosed in 31 patients (7·7 per cent), with a 10·4 per cent leak rate in the C-seal group and 5·0 per cent in the control group ( P = 0·060). Male sex showed a trend towards a higher leak rate ( P = 0·055). Construction of a defunctioning stoma led to a lower leakage rate, although this was not significant ( P = 0·095). Conclusion: C-seal application in stapled colorectal anastomoses does not reduce anastomotic leakage. Registration number: NTR3080 (http://www.trialregister.nl/trialreg/index.asp ). Abstract : Not effective